The Role of Blastocystis spp. in the Etiology of Gastrointestinal and Autoimmune Diseases - Oliwia Pawelec-Pęciak; Natalia Łanocha-Arendarczyk; Konrad Grzeszczak; Danuta Kosik-Bogacka (Pathogens)
Blastocystis spp. has been linked to gastrointestinal symptoms, yet its pathogenicity remains uncertain. In addition, the roles of virulence factors, pathogenic potential, and host-specific traits associated with symptomatic infections are still not well understood. The growing number of immunocompromised patients has contributed to an increasing prevalence of Blastocystis spp. infections, which may be implicated in the development of various inflammatory diseases, including irritable bowel syndrome (IBS), colorectal cancer, and autoimmune disorders such as Hashimoto’s disease and ulcerative colitis. However, the presence of nonspecific symptoms often complicates diagnosis. This study aimed to present current data on the impact of Blastocystis spp. on the development and progression of gastrointestinal and autoimmune diseases, as well as to explore potential treatment options for Blastocystis spp. infections. A literature review was conducted to analyze the role of Blastocystis spp. in the pathogenesis of specific diseases and to investigate potential mechanisms of its interaction with the host organism. Advances in diagnostic techniques, particularly PCR, allow not only for the detection of Blastocystis spp. but also for the identification of specific subtypes, improving treatment precision. Beyond conventional therapies like metronidazole, there is a growing emphasis on alternative treatments, including the use of medicinal plants and probiotics.